Peran Komunikasi Interpersonal dalam Penyelesaian Konflik di Media Sosial - Savira, Rini; Nasichah; Labiq, Ahmad (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2023)
The phenomenon of long-distance communication is something that often occurs in the era of the rise of technology. In conducting interpersonal communication, there is communication or a process of exchanging information, ideas, opinions, and feelings that occur between two or more people and is usually not regulated formally. In addition, there are experts who state that long-distance communication is considered a process of exchanging information that is less effective because the five senses are not involved in the process of interpreting messages. This, there is a risk of causing misunderstandings and increasing the possibility of obstacles in the communication process Therefore, this study discusses how the impact of interpersonal communication barriers affects couples who are far apart in managing conflict. This research is a type of qualitative research that aims to determine the impact of interpersonal communication barriers on long-distance couples in managing conflict. The process of data analysis is based on the theory of interpersonal communication, conflict management. The impact on the conflict management process is the delay in the process of finding a solution between the two parties so that the tendency for this type of conflict management to be destructive in some cases.